2020
DOI: 10.1021/acs.jced.9b01036
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Determination, Model Correlation, and Solvent Effect Analysis of Nisoldipine in Different Solvent Systems at a Series of Temperature

Abstract: In this work, the solubility of nisoldipine in ethyl acetate, toluene, 1-butanol, 1-propanol, ethanol, acetonitrile, water, 2-propanol, cyclohexane, and two binary solvents mixtures (2-propanol/ethanol + water) at the temperature ranging from 278.15 to 318.15 K, solvent effect in a monosolvent system, and model correlation are studied. The solubility of nisoldipine is positively correlated with temperature. At a certain temperature, the subsequence of solubility of nisoldipine was of the order ethyl acetate (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 30 publications
(50 reference statements)
0
38
0
Order By: Relevance
“…Excluding intermolecular interactions, another two factors consisting of the molecular structure and viscosity may also influence the solubility behavior of NALP. Compounds with similar structures are more likely to be dissolved by each other, i.e., the rule of “like dissolves like”, , which could enhance the solubility of the solute. It can be observed that the solubility magnitudes in ketones (acetone and 2-butanone) are higher than those in esters (methyl acetate and ethyl acetate), which could be attributed to the same carbonyl groups possessed by the molecular structures of both ketones and NALP.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding intermolecular interactions, another two factors consisting of the molecular structure and viscosity may also influence the solubility behavior of NALP. Compounds with similar structures are more likely to be dissolved by each other, i.e., the rule of “like dissolves like”, , which could enhance the solubility of the solute. It can be observed that the solubility magnitudes in ketones (acetone and 2-butanone) are higher than those in esters (methyl acetate and ethyl acetate), which could be attributed to the same carbonyl groups possessed by the molecular structures of both ketones and NALP.…”
Section: Resultsmentioning
confidence: 99%
“…Except for solvent–solute and solvent–solvent interactions, the dissolution behavior of Boc-L-proline could also be influenced by the molecular structures of the solvent and solute. Compounds that have similar chemical constructions are more likely to be dissolved by each other, which may result in the increase in solubility. , There are three methyl groups on the tert -butoxycarbonyl group of the Boc-L-proline molecule, which may lead to the strong association between methanol (also contains methyl) and Boc-L-proline molecules. This may be the reason for the highest solubility of methanol among the 14 solvents.…”
Section: Results and Discussionmentioning
confidence: 99%
“…By comparing the solubility data and viscosity values of the selected solvents, it is found that the solubility in eight alcohol solvents, two ketone solvents, and two ester solvents decreased with the increase of viscosity. Compounds with similar structures can dissolve each other better and lead to the enhancement of the solubility, which is the principle of “like dissolves like”. , It can be inferred that the solubility in acetone and 2-butanone is higher than that in methyl acetate and ethyl acetate, which may be because the same carbonyl group existed in the ketones and NAM molecules. In addition, the high solubility of 1,4-dioxane may be speculated as follows: NAM can be used as a hydrogen bond donor and a hydrogen bond acceptor, leading to the formation of intramolecular hydrogen bonds, thus becoming a ring structure.…”
Section: Resultsmentioning
confidence: 99%